A Q Methodology Study: How Do Coaches Foster the Coaching Relationship? - Elizabeth Crosse (International Journal of Evidence Based Coaching and Mentoring, 2019)
There have been numerous studies which demonstrate the importance of the coaching relationship and its relevance in ensuring the successful outcome of the coaching process. However, there has been little exploration of the coach’s perspective; how do they make sense of their ability to foster coaching relationships in practice? Q-methodology was used to elicit possible meaning schemes that underpin this capability. Four distinct viewpoints were identified which provided the foundation for a ‘relationship styles framework’ that reflected the range of ways coaches work with complexity, ambiguity and holistic understanding in the management of coach client relations.